Inferior retinotomy and silicone oil tamponade for recurrent inferior retinal detachment and grade C PVR in eyes previously treated with pars plana vitrectomy or scleral buckle. Issue 1 (December 2015) - Mancino, Raffaele; Aiello, Francesco; Ciuffoletti, Elena; Di Carlo, Emiliano; Cerulli, Angelica; Nucci, Carlo
Abstract Background One of the most challenging problems in vitro-retinal surgery is the recurrence of retinal detachment in the context of high-grade proliferative vitreoretinopathy (PVR). The aim of our retrospective study was to assess the surgical outcomes of pars plana vitrectomy, 180° inferior retinotomy and silicone oil tamponade combined with phacoemulsification and IOL implantation for recurrent inferior retinal detachment with grade C PVR in phakic eyes. The study was carried out at tertiary referral centre - University Hospital of Rome "Tor Vergata". Methods Retrospective analysis of 33 eyes affected by recurrent inferior retinal detachment and grade C PVR after primary encircle scleral buckling (SB group – 12 eyes), or pars plana vitrectomy (PPV group – 21 eyes). All patients subsequently underwent PPV and silicone oil tamponade at our Institution. The first outcome measure was retinal reattachment, and second outcomes were reoperation rates, best-corrected visual acuity (BCVA) and postoperative complications. Results All patients in the SB group and 19 (90 %) patients of the PPV group achieved retinal reattachment. Final BCVA was better in the SB group (p  = 0.045). Two eyes in the PPV group required a third vitrectomy with heavy silicone oil tamponade. Postoperative complications included silicone oil in a deep anterior chamber (3 eyes in each group), untreatable hypotony in 1 eye in the PPV group (that led to enucleation due to phthisis bulbi), and elevated intraocular pressure in 3 patients (2 eyes in the PPV group). Conclusions Phacoemulsification with IOL implant, PPV with silicone oil tamponade associated with 180° inferior retinotomy may lead to better anatomical success in patients who have previously undergone SB procedure for inferior retinal detachment repair compared with eyes that underwent a primary PPV.